Use of cargo delivery process model for the assessment of logistics service quality - Kyrychenko, Hanna; Nesterenko, Halyna; Avramenko, Svetlana; Lytvynenko, Sergiy; Yanovsky, Petro; Lytvynenko, Larysa (International Journal of Engineering and Technology, 2018)
The paper proposes the method of forecasting the time of operations with a wagon and a cargo, which is carried out using the cargo delivery process model taking into account possible scenarios of the process and deviation from the forecast and technological standards. One of the concepts of the model is the average deviation from the forecast. This method for the first time allowed considering the conditions of real operational work when forecasting control points of cargo delivery process stages. Data on deviation is proposed to be stored in the database of the automated system for forecasting. The paper also proposes an estimation of deviations at all stages of transportation using linguistic definitions of the states, which allows quantifying the indicator, such as the quality of transportation. The given method allows forecasting the time control points of the scheduled cargo delivery stages considering the conditions of real operational work. One of the prospects for using the above method is the ability of information interaction of the transportation participants, namely, in the part of exchange and processing of operation monitoring data, data on deviations from the forecast and standards, as well as the exchange of delivery quality assessment data.Â